The social and psychological functions of responses to climate change - Leviston, Zoe (Curtin University, 2013)
Climate change is the most pressing environmental threat faced by humans, yet responses – individually, collectively, and politically – have frequently lacked urgency. Why a threat of such magnitude should meet with inaction is a topic of growing conjecture among social science researchers. Social psychologists in particular have increasingly focused on the possible psychological mechanisms underlying denial and scepticism of anthropogenic climate change. I argue that all responses to climate change can be considered rational and adaptive, because these responses (be they opinions, emotions, or behaviour) afford the individual functional value.In this thesis, I examine what underlies the discordance between climate change threat and response by applying a functional analysis to responses associated with climate change. This analysis is theoretically guided by a motivated social cognition approach. I use the term to refer to theories and perspectives that assume that people’s values, attitudes, and beliefs have motivational underpinnings, and satisfy certain psychological and social needs. These motivations affect reasoning and belief and attitude formation by biasing how information is processed. The approach incorporates accounts such as motivated reasoning, interpersonal and social identity theories, social and system-level legitimacy theories, moral disengagement, and Terror Management Theory. Drawing upon these accounts, I construct a framework detailing the various goals and needs that responses to climate change might function to fulfil.Five main functional areas are identified: the reduction of internal psychological discomfort, self-image and self-esteem maintenance, the maximisation of positive affect, social-system justification, and effort reduction. To test aspects of the framework, I conducted two online national surveys: one in July-August 2010 (N = 5036), the other in July-August 2011 (N = 5030). A total of 1355 respondents completed both surveys. Respondents were asked about their beliefs, opinions, attitudes, and behaviours relevant to climate change, as well as individual difference measures, their levels of support for climate change policy, their emotional responses, and personal and image associations with climate change. In addition, four workshops (total N = 52) were undertaken in December 2010 and March 2011. These workshops were designed to elicit implicit associations and attendant emotions associated with climate change imagery drawn from the national surveys.Analyses of national survey data revealed several key findings: * The scientific consensus that climate change is happening, and is mostly caused by human activity, is not reflected in the opinions of the broader community; * While opinions about the causes of climate change are important in understanding pro-environmental behaviour, considerable variation in behaviour exists within opinion-types; * Negative high-arousal emotions are linked to climate change acceptance and pro-environmental behaviour; * Levels of moral engagement are central to action on climate change, and mediate the link between opinions and behaviour; * Those sceptical of climate change still consider big-polluting countries and multi-national corporations as partly responsible for both causing and responding to it; * Estimates about what the Australian community thinks about climate change differ markedly from actual opinions, and nearly everybody overestimates the levels of ‘climate change denial’ in the Australian community; * Underlying ideological values associated with system justification explain relationships with climate change responses above and beyond political preferences.Analyses of both the survey and workshop data revealed that politicians dominate who we associate with climate change, while scientists and people close to us are less commonly associated with climate change. Images commonly associated with climate change were broad and remote, although national-level impacts of climate change were salient for many people.Together, the results support the idea that responses function to fulfil different needs and goals for individuals, such as a need for social support, the negation of guilt and existential anxiety, maintaining a coherent self-identity, feeling morally adequate, and seeing prevailing social and economic systems as just. I conclude the thesis by modelling the psychological processes involved in fulfilling these needs and goals, and the expressions through which they might be observed with respect to responses to climate change. In particular, the model articulates how the implicit associations of individuals are shaped by societal, group, and intra-individual forces, and by the biased searching of sets of rules and beliefs. A series of recommendations for climate communicators is provided, including framing climate change in such a way as to appeal to competing needs and goals concurrently, alongside an overview of future research directions, and an explanation of why I probably won’t ride my bicycle to work tomorrow.